Novel framework using dynamic passphrase towards secure and energy-efficient communication in MANET - Chethan B. K.; M. Siddappa; Jayanna H. S. (International Journal of Electrical and Computer Engineering (IJECE), 2020)
At Mobile Adhoc Network (MANET) has been long-researched topic in adhoc network owing to the associated advantages in its cost-effective application as well as consistent loophopes owing to its inherent charecteristics. This manuscript draws a relationship between the energy factor and security factor which has not been emphasized in any existing studies much. Review of existing security approaches shows that they are highly attack specific, uses complex encryption, and overlooks the involvement of energy factor in it. Therefore, the proposed system introduces a novel mechanism where security tokens and passphrases are utilized in order to offer better security. The proposed system also introduces the usage of an agent node which communications with mobile nodes using group-based communication system thereby ensuring reduced computational effort of mobile nodes towards establishing secured communication. The outcome shows proposed system offers better outcome in contrast to existing system.